Investigation of DC glow discharge in CO₂ using optical emission spectroscopy - Lisovskiy, V.A.; Krol, H.H.; Dudin, S.V. (Вопросы атомной науки и техники, 2018)
The results of investigations of a glow discharge in carbon dioxide by the method of optical emission spectroscopy are presented. Processes in negative glow, positive column and anode glow are considered in detail. In the negative glow, bright radiation lines of both atoms and molecules and their ions are observed: O, O⁺ , CO, O₂, CO⁺ and molecular continuum. In the positive column, a weak continuum and emission lines of CO₂, CO, and O₂ molecules are seen. The emission lines of CO molecules dominate in the anode glow against the background of the continuum, and also lines of molecular and atomic oxygen are visible. Axial intensity distributions of a number of lines are presented for the entire discharge gap between the cathode and the anode.